Floating marine litter as a raft for drifting voyages for Planes minutus (Crustacea: Decapoda: Grapsidae) and Liocarcinus navigator (Crustacea: Decapoda: Polybiidae). Issue 1 (15th July 2017) - Tutman, P.; Kapiris, K.; Kirinčić, M.; Pallaoro, A.
Abstract: The Columbus crab Planes minutus and Arch-fronted swimming crab Liocarcinus navigator, within their distribution ranges in the Mediterranean, were found rafted on plastic macro-litter floating on the open south Adriatic. While P. minutus was recorded from inanimate flotsam outside of the Mediterranean, L . navigator is herein reported for the first time on floating marine litter. The role of floating litter as habitat or as a dispersal agent for marine invertebrates has received quite attention however, records of decapod crabs drifting on litter has been relatively sparse. Our results suggests that vast quantities of floating debris, comprised primarily of non-biodegradable plastic polymers, probably will augment natural floating substrates in the marine environment, potentially facilitating the spread of invasive species. The dispersion of rafting crabs through floating debris should be investigated given the high potential ecological risk of invasion by exotic species due to the increase in waste production (ecological risk assessment). Highlights: First case of Liocarcinus navigator floating on marine litter was reported. New record of Planes minutus rafting on floating plastic debris was also presented. Increase of floating plastic probably will augment rafting substrates in the sea. Dispersion of marine organisms through floating debris should be controlled.